Some Higher Order Algorithms for Solving Fixed Point Problems - Waheed, Asif; Din, Syed Tauseef Mohyud; Zeb, Muhammad; Usman, Muhammad (Communications in Mathematics and Applications, 2018)
In this paper, some higher order algorithms have been introduced for solving fixed point problems. These algorithms have been developed by Homotopy Perturbation Method. New algorithms are tested on diversified nonlinear problems. The results are very promising and useful. Comparison of numerical results along with existing proficient techniques explicitly reflects the very high level of accuracy of developed iterative schemes.